Towards Dual Use of Volunteers in Small and Large Emergencies: Comparing Emerging Volunteer Initiatives - Yusuf Mohamed, Mohamud; Pilemalm , Sofie (Proceedings of the International ISCRAM Conference, 2025)
In crisis management, most studies on Information and Communication Technology (ICT) focus on spontaneous volunteers using social media for information dissemination or self-deployment to the incident site. However, there is also growing research on more organized forms where volunteers act as first responders to small, frequent emergencies. They are potential useful but unused resources in larger crises contributing to community and society resilience. To identify their potential for dual use, we must first understand their contributions to small-scale emergencies. This study describes and compares different volunteer initiatives in Sweden in terms of recruitment, willingness to collaborate with other volunteers, tasks, ICT utilization, challenges and needs. The findings indicate that volunteers possess significant capacity for responding to small-scale emergencies, which can be utilized for large-scale crises. They demonstrate a strong willingness to collaborate with other volunteers, have dual roles with diverse skillsets and can stay a long-time span at incident sites supporting victims, e.g., distributing food and medicine.